Petrogênese do stock granítico Monte Alegre, noroeste do domínio Macururé, faixa sergipana - Oliveira, Ana Carolina Soares de (2014)
The Monte Alegre Stock is a granitic intrusion (5 km2) in the Macururé Domain of the Sergipe Belt. This belt is a Neproterozoico fold system, in this context, the Monte Alegre Granite Stock integrates an expressive set of granites assumed to be post-tectonic the climax of the Brasiliano Cycle. The rocks of this stock were grouped into three petrographic facies: Porphyritic Facies, Leucocratic Equigranular Facies and Enclaves Facies, with an Equigranular Leucocratic Facies that dominates. Petrographic studies have indicated in stock existence quartz biotite monzonite, granite muscovite, granite with muscovite and biotite and subordinate manner, monzodiorites quartz. The mineralogy is essential andesine / oligoclase, alkali feldspar, quartz, muscovite , biotite and accessory apatite, magmatic epidote, titanite, zircon, carbonate and opaque . The enclaves are monzonite and monzodiorite, with the predominant mafic mineral bearing biotite and diopside.The geochemichal data indicates that the rocks the are potassic alkaline, and the enclaves are metaluminous, the granites and quartz - monzonite are peraluminous. In Harker diagrams we observed positive correlations between increasing silica and K2O, Al2O3 and Na2O, which expresses the fractionation of plagioclase, mafic minerals and accessories. The total REE values tend to decrease with fractionation and this is also observed in the negative anomalies of Eu. In the tectonic settings diagrams the granites occupy the field of syn- collisional rocks while the quartz-monzonite and enclaves occupy the field of volcanic-arc granite. The petrogenetic model proposed for the formation of porphyritic rocks is the mixture, in varying degrees, between mafic and felsic magma materialized by the presence of syn-plutonic dikes . The muscovite granite are interpreted as resulting from partial melting of metasedimentary rocks when the enplacement of the porphyritic rocks.